2021
DOI: 10.1128/jmbe.v22i1.2425
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Curricular Shifts on Learning Gains on the Microbiology for Health Sciences Concept Inventory

Abstract: As a validated assessment, the Microbiology for Health Sciences Concept Inventory (MHSCI) is a valuable tool to evaluate student progress in health sciences microbiology courses. In this brief analysis, we survey MHSCI faculty users and report student MHSCI scores to determine the impact on student learning gains of the COVID-19 pandemic and subsequent quarantine in spring 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Together with Harmon et al (2021), this body of research has demonstrated the dramatic changes undertaken by gross anatomy educators in response to Covid‐19 during May–December, 2020. This paradigm‐shifting pedagogy in gross anatomy and across higher education (García‐Morales et al, 2021; Pokhrel & Chhetri, 2021) during 2020 forced educators in gross anatomy (Evans et al, 2020) as well as other basic medical science disciplines (Bzowyckyj et al, 2021; Seitz & Rediske, 2021; Zhang et al, 2021) to reassess the best ways to deliver higher education. It is unknown whether the changes will become a common practice after Covid‐19 is better controlled or vanquished.…”
Section: Discussionmentioning
confidence: 99%
“…Together with Harmon et al (2021), this body of research has demonstrated the dramatic changes undertaken by gross anatomy educators in response to Covid‐19 during May–December, 2020. This paradigm‐shifting pedagogy in gross anatomy and across higher education (García‐Morales et al, 2021; Pokhrel & Chhetri, 2021) during 2020 forced educators in gross anatomy (Evans et al, 2020) as well as other basic medical science disciplines (Bzowyckyj et al, 2021; Seitz & Rediske, 2021; Zhang et al, 2021) to reassess the best ways to deliver higher education. It is unknown whether the changes will become a common practice after Covid‐19 is better controlled or vanquished.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these negative student experiences, some studies have reported small increases in student grades in Spring 2020 compared to similar courses in previous years (Gonzalez et al, 2020;Loton et al, 2020;Bawa, 2021). Similarly, a nationwide analysis of scores on a microbiology concept inventory showed no decline and even some improvement in student learning gains in Spring 2020 (Seitz and Rediske, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…The transition from formal face-to-face learning to virtual learning is challenging for all undergraduate students, especially those who aspire to major in the field of biological sciences (Seitz, 2021). The coronavirus disease (COVID-19) pandemic has introduced educators and curriculum developers to novel methods of addressing education for undergraduate microbiology students (Lischer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%